Comprehensive Utilization of Magnesium Slag by Pidgeon Process - Wu, Lan'er (SpringerBriefs in Materials, 2021)
This open access book introduces the magnesium resources in the world and the layout of this industry, the harmless handling/recycling of magnesium slag, and the process of magnesium silicothermic reduction (Pidgeon process) to produce the slag. Examples and experimental data in this book are from the author group's research programs, as well as the recent researches in China. The book could provide precious reference to scientists and engineers in the field of recycling and environment friendly use of the industrial solid wastes. It could also be used for researchers and students who are interested in relevant field.